2021
DOI: 10.1111/inr.12739
|View full text |Cite
|
Sign up to set email alerts
|

Unmet informatics needs of nurses regarding the use of personal smartphones in the workplace

Abstract: Aims This study aimed to investigate the differences in practices, policies, and perceptions of nurses regarding work‐related utilization of smartphones in acute‐care settings. Background Mobile devices utilizing emerging technology are widely used in acute‐care settings; however, concerns such as potential distraction, improper use, and negative impact on the nursing image in clinical practice remain valid. Methods Nurse managers (n = 8) and nurses (n = 181) were enrolled from eight academic tertiary hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These findings are consistent with Korean nurses' reported use of their personal digital devices within acute care. 20 Researchers reported that personal smartphone use among acute care Korean nurses was common and frequently used for pragmatic reasons similarly reported in this study. Korean nurses also used their smartphones to capture photos of patient data and to seek on-line information.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…These findings are consistent with Korean nurses' reported use of their personal digital devices within acute care. 20 Researchers reported that personal smartphone use among acute care Korean nurses was common and frequently used for pragmatic reasons similarly reported in this study. Korean nurses also used their smartphones to capture photos of patient data and to seek on-line information.…”
Section: Discussionsupporting
confidence: 61%
“…Enhanced and efficient communication among the healthcare team has the potential to contribute to improved patient care and safety yet at the same time may challenge patient information safety in terms of breaches to information privacy and confidentially. 20,29 Opportunities for future research exist to investigate RN and RPN use of personal devices for communication among the broader healthcare team and to understand how patient information safety is being addressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations